Adding value to tuber crops: Unlocking new opportunities - Sajeev, M S; Jyothi, A N; Krishnakumar, T; Pradeepika, C (Indian Horticulture, 2025)
ICAR-Central Tuber Crops Research Institute has developed a range of innovative technologies for value addition and postharvest utilization of tropical tuber crops. Rich in starch with unique physico-chemical properties, these crops are processed into extruded foods like pasta, noodles, spaghetti, kurkure-type snacks and fried products from composite flours with good nutritional and sensory quality. Cassava starch, being renewable, abundant, low-cost, film-forming and biodegradable, is a promising material for eco-friendly packaging and a key feedstock for bioethanol production. Modified starches with tailored properties further widen applications, including superabsorbent gels for healthcare and agriculture, nanocomposites for sustained drug delivery, corrugating adhesives, graft copolymers for oil drilling, and textile sizing. Anthocyanins from sweet potato tubers and leaves provide safe natural food colourants, while cassava stems and leaves can be used for particle boards and biopesticides. Thus, tropical tuber crops offer vast opportunities for sustainable food and industrial applications.